One-Year Adherence to Continuous Positive Airway Pressure With Telemonitoring in Sleep Apnea Hypopnea Syndrome: A Randomized Controlled Trial - Contal, Olivier; Poncin, William; Vaudan, Stéphanie; De Lys, Angélique; Takahashi, Hiromitsu; Bochet, Séverine; Grandin, Stéphane; Kehrer, Philippe; Charbonnier, Florian (Frontiers in Medicine, 2021)
Study Objective: Telemedicine (TM) for continuous positive airway pressure (CPAP) treated patients may save health-care resources without compromising treatment effectiveness. We assessed the effect of TM (AirView Online System, ResMed) during the CPAP habituation phase on 3-month and 1-year treatment adherence and efficacy in patients with moderate-to-severe obstructive sleep apnea (OSA). Methods: At CPAP initiation, 120 patients diagnosed with OSA were randomized to either usual care (UC) or TM during the habituation phase (clinical registration: ISRCTN12865936). Both groups received a first face-to-face appointment with a sleep care giver at CPAP initiation. Within the following month, 2 other physical visits were scheduled in the UC group whereas 2 phone consultations were planned in the TM group, in which CPAP parameters were remotely adapted. Additional physical visits were programmed at the patient’s request. Face-to-face consultations were scheduled at 3 months and 12 months after CPAP initiation. The primary outcome was the mean CPAP daily use over the course of 12 months. Results: Five out of 120 patients did not attend the first follow-up visit and were lost to follow-up. On the remaining 115 participants, CPAP parameters and treatment efficacy (daytime sleepiness and depression) did not differ between groups at any time points. Twenty of 58 patients stopped CPAP therapy in the UC group versus 14 of 57 in the TM group (p=0.24). In per protocol analysis, mean (95%CI) daily CPAP use among 86 patients still using CPAP at 12 months was 279 (237 to 321) min in the 38 patients on UC and 279 (247 to 311) min in the 43 patients on TM, mean difference (95%CI) 0 (-52 to 52) min, P=0.99. Total consultation time per patient was not different between groups, TM: 163 (147 to 178) min, UC: 178 (159 to 197) min, difference -15 (-39 to 9) min, p=0.22. Conclusions: Telemedicine during the CPAP habituation phase did not alter daily CPAP use or treatment adherence and did not require more healthcare time. Telemedicine may support clinic attendance for CPAP titration.